Determining the Mass Grave Delineation in Sandy Soils Using Ground Penetrating Radar, a Laboratory Experiment - Chlaib, Hussein Kh.; Ramthan, Ali (Iraqi Journal of Science, 2025)
Identifying the mass graves’ boundaries is a significant step in mass graves’ preparatory procedures. A laboratory experiment was conducted to determine the effectiveness of ground penetrating radar in identifying mass graves and delineating their boundaries in sandy soil. A GSSI SIR-3000 GPR system with a 1.5 GHz antenna was used for the experiment. Eight GPR profiles were run over a 0.16m-deep wooden sandbox that contained buried bones to simulate the mass grave. All GPR profiles were processed using zero time, background removal, and filters to produce clearer, more accurate, and interpretable GPR data. This geophysical technique showed its assistance and effectiveness in locating the mass grave and tracking its delineation within sandy soils (desert environment). It was easy to locate the boundary between the simulated human remains (bones) and the surrounding materials (sand) due to the differences in their dielectric constant due to the chemical and physical differences that will convert to different reflections. Changing the antenna configurations (polarizations) in the GPR survey over the simulated target showed a clear difference in the reflection or the clarity of the “target”. The calculated depth of the buried bones was very close to the actual depth. This novel application of the GPR will help in Iraqi mass grave investigation, recovery and excavation in desert environments.